Damage Identification Method with Structural Frequency Data from Modal Test - Du Jian-hua; Ouyang Zhiwei; Zhao Yangdong (Communications - Scientific letters of the University of Zilina, 2009)
Testing and analysis technology based on vibration mode is a common method to structural health monitoring and checking. This paper deduces the damage factor used for structural damage evaluation based on test frequency of structure, makes a finite element numerical simulation using ANSYS software and model test to a pressure pipe. Here a stiffness reduction method is utilized to reproduce the damage state of a single-point and multiple-point, damage identification is carried out with a FEM model of redundant pipe. Meanwhile, a model experiment system is designed to validate the efficiency of damage factor with cutting-groove to simulate damage states. Numerical and experimental results show the proposed damage factor is theoretically breviate, simple realization and high-accuracy performance, therefore, it has a good usage prospect in the implementation of structural damage monitoring and identification.